UJI EFEK TONIKUM EKSTRAK ETANOL DAUN KAMBOJA (Plumeria sp.) PADA MENCIT (Mus muscullus) - Panji Ratih Suci (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2021)
Indonesia, which is famous for its rich flora, stores various plants that can be used as medicine or decoration. Flavonoid compounds in several studies have been reported to trigger stimulants in the heart, allowing the flavonoid compounds in frangipani leaves to be used as a tonic effect. Objective: This study aims to determine what is the most effective dose of either 3.5g/KgBW, 5.25g/KgBW and 7g/KgBW of frangipani leaf extract (Plumeria sp.) when used as a tonic in male mice (Mus muscullus). ), and to find out how the effect of giving the dose variant compared to the positive control (caffeine) and negative (CMC 0.5%) gave a tonic effect on the length of time swimming in male mice (Mus muscullus). Methods: This study used the swimming test method which was carried out on male mice treated with 0.5% CMC as a negative control and caffeine as a positive control. Then look at the time on the swimming endurance of mice. Results: This study showed that the treatment group of frangipani leaf ethanol extract at a dose of 3.5 g/Kg BW, 5.25 g/KgBW, and 7 g/KgBW had an increase in the swimming survival time of male mice from before the test solution was administered. The most effective dose is 7g/KgBW which has an average swimming time of 8 minutes 9 seconds which is almost close to the average swimming time of caffeine as a positive control of 10 minutes 5 seconds. Strengthened by the SPSS test which has a significance of 0.00 which indicates the effect of dosing on the swimming time of male mice (Mus muscullus).